They were strong and good - Lawson, Robert, 1892-1957. ([New York] The Viking press, 1940)
Relates the story of the author's grandparents and parents, who, though not famous, helped build the United States.
Illustrated t.-p. and lining papers.
"This is the story of my mother and my father and of their fathers and mothers."--Foreword.
"First published September 1940."
Keywords: Caldecott Medal; Families